2019
DOI: 10.3390/molecules25010139
|View full text |Cite
|
Sign up to set email alerts
|

New Dammarane-Type Triterpenoid Saponins from Panax notoginseng Leaves and Their Nitric Oxide Inhibitory Activities

Abstract: Inflammation is a very common and important pathological process that can cause many diseases. The discovery of anti-inflammatory drugs and the treatment of inflammation are particularly essential. Dammarane-type triterpenoid saponins (PNS) were demonstrated to show anti-inflammatory effects in the leaves of Panax notoginseng. Chromatographies and spectral analysis methods were combined to isolate and identify PNS. Moreover, the nitric oxide (NO) inhibitory activities of all compounds were examined in lipopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
(24 reference statements)
0
9
1
Order By: Relevance
“…Different from our previous research [ 7 , 8 ], a new 12,23-epoxydammarane skeleton has been found in this paper, and its superior in vitro anti-inflammatory activites, compared with the other compounds reported earlier [ 7 , 8 ], made it more promising to become the target of new anti-inflammatory drugs. What is more, the results of the Western blot assays provided more evidence for its further development.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Different from our previous research [ 7 , 8 ], a new 12,23-epoxydammarane skeleton has been found in this paper, and its superior in vitro anti-inflammatory activites, compared with the other compounds reported earlier [ 7 , 8 ], made it more promising to become the target of new anti-inflammatory drugs. What is more, the results of the Western blot assays provided more evidence for its further development.…”
Section: Discussioncontrasting
confidence: 91%
“…Moreover, the planar structure of 1 was determined by the long-range correlations displayed from H 3 -18 to C-7–9, C-14; H 3 -19 to C-1, C-5, C-9, C-10; H 3 -21 to C-17, C-20, C-22; H 3 -23 to C-12, C-24, C-25; H 3 -26 to C-24, C-25, C-27; H 3 -27 to C-24–26; H 3 -28 to C-3–5, C-29; H 3 -29 to C-3–5, C-28; H 3 -30 to C-8, C-13–15; H-1′ to C-3; H-1″ to C-20; H-1‴ to C-6″ in its HMBC experiment ( Figure 2 ). The chemical shifts of protons and carbons in A and B rings resembled notoginsenoside NL-A 1 [ 7 ], which suggested that the A and B rings of notoginsenoside NL-I ( 1 ) were identical to it. Moreover, the NOE correlations observed between δ H 1.49 (H-9) and δ H 3.67 (H-12); δ H 3.67 (H-12) and δ H 3.22 (H-17), 4.86 (H-23); δ H 3.22 (H-17) and δ H 4.86 (H-23) in the NOESY spectrum ( Figure 2 ) indicated that H-12 and H-23 were α-orientation, like H-9, while the β-orientations of H-13 and 21-CH 3 were confirmed by the cross peaks observed between δ H 1.59 (H-13) and δ H 0.94 (H 3 -18), 1.51 (H 3 -21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Dammarane-type triterpenoid saponins could inhibit NO activities in a dose-dependent manner. 17 Treatment of porcine circovirus 2-infected porcine lung cells with PNS resulted in a significant reduction in intracellular NO content and xanthine oxidase activity, which suggested that PNS could regulate the oxidative stress of immune cells. 18 PNS decreased serum MDA, lactate dehydrogenase, myocardial tissue superoxide dismutase, and reactive oxygen species.…”
Section: Discussionmentioning
confidence: 97%
“…By summarizing the structure-activity relationship of saponins, the anti-inflammatory activities of the compounds were found to be closely related to the types of substituted sugar groups and to increase with the number of substituted sugar groups. In addition, the positions and number of hydroxyl groups on the mother nucleus have a strong influence on the anti-inflammatory activities of saponins [ 46 ].…”
Section: Potential Effects Of Herbal Active Ingredients On Experimental Alimentioning
confidence: 99%